PENGARUH KUALITAS SISTEM DAN KUALITAS INFORMASI TERHADAP MANFAAT BERSIH DENGAN INTENSITAS PENGGUNAAN SEBAGAI VARIABEL MEDIASI - Yuyut Krisdiantoro; Imam Subekti; Yeney Widya Prihatiningtias (Universitas Negeri Malang, 2018)
This study aims to provide empirical evidence of the influence of system quality and information quality on net benefits mediated by the intensity of use. Data collection methods in this study used a survey of respondents who served as financial managers, users of Sistem Informasi Manajemen Pengadaan Langsung (SIMPeL) at offices within the Ministry of Finance in East Java Province and obtained 97 respondents. Data were analyzed by using Structural Equation Model - Partial Least Square (SEM-PLS). The result shows several findings. Firstly, the quality of a good system will affect the intensity of the use of the system and can provide added value in the form of improvements to the performance of individuals and organizations. The second finding shows that the quality of information affects the improvement of individual and organizational performance. Thirdly, the quality of information does not affect the intensity of use. Lastly , the intensity of use has no effect on the improvement of individual and organizational performance. The result of this study can be used as consideration in making improvements in the implementation and development of Sistem Informasi Manajemen Pengadaan Langsung (SIMPeL)